Strategic investment in international gas transport systems - Franz Hubert (EIB Papers, 2007)
This paper provides a quantitative analysis of power relations and strategic investment in the transport system for Russian gas. First, we analyse how the architecture of the transport system determines Russias bargaining power vis-à-vis (potential) transit countries. By applying the Shapley value as a solution for multilateral bargaining we find that competition between transit countries is of little strategic importance compared to direct Russian access to its customers in Western Europe. Second, we develop a dynamic model of strategic investment. We find that the failure to include Belarus and Ukraine into a framework for international contract enforcement resulted in underinvestment in cheap pipelines and overinvestment in expensive ones. As capacities are increased to gain leverage over transit countries, customers in Western Europe benefit in terms of lower prices and higher supply security.
Keywords: 330; Gasleitungstransport; Betriebliche Investitionspolitik; International; Europa; Russland; Asien